Out of the blue : new short fiction from Iceland - Mitsios, Helen; Sjón, 1962- (University of Minnesota Press, 2017)
This extraordinary collection, the first anthology of Icelandic short fiction published in English translation, features work by twenty of Iceland's most popular and celebrated living authors--including Andri Snær Magnason, Jón Kalman Stefánsson, Kristín Ómarsdóttir, and Auður Jónsdóttir--granddaughter of Halldór Laxness, who won the 1955 Nobel Prize in Literature. Celebrated in Europe and Scandinavia but less known in the English-speaking world, these writers traverse realms of darkness and light that will be familiar to readers who have fallen under the spell of Scandinavian fiction. While uniquely Icelandic in topography and tenor, with a touch of the island's supernatural charm, the stories traffic in the enduring and universal complexities of human nature. Here is a fictional universe where the ghosts of Vikings and spirits tread, volcanoes grumble underfoot, and writers trip the Northern Lights fantastic across the landscape of the Icelandic imagination. At long last, readers can enjoy award-winning stories now expertly rendered into English by the country's most renowned translators. In "Killer Whale" a father contemplates euthanasia for a terminally ill child, in "Self Portrait" a vacationing family in Spain crosses paths with migrants, in "Escape for Men" a woman searches for an ex-lover in the South of France, and in "The Most Precious Secret" the nature of artists and the art world is mercilessly revealed. Both the Viking myths of Iceland's forefathers and the cutting-edge modern world of the country today are brilliantly alive in these remarkable and original stories. This collection is an excursion to an island where almost two million travelers descend yearly on a population of 345 thousand natives. Iceland is the place Björk calls home, the location where Game of Thrones was filmed--a place with open lava fields, glaciers, and iceberg lagoons among other natural wonders that is becoming one of the "hottest" tourist destinations on earth. Out of the Blue transports readers to Iceland's timeless and magical island of Vikings and geographical wonders, and it promises to be a seminal collection that will define Icelandic literature in translation for decades to come.